Genotipagem dos isolados de Giardia duodenalis de humanos e de cães na colônia de pescadores de Porto Said, Botucatu, São Paulo - David, Érica Boarato [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Several species of protozoa cause acute or chronic gastroenteritis in humans, worldwide. The burden of disease is particularly high among children living in developing areas of the world, where transmission is favored by lower hygienic standards and scarce availability of safe water. However, asymptomatic infection and polyparasitism are also commonly observed in poor settings. Here, we investigated the prevalence of intestinal protozoa in two small fishermen villages, Porto Said (PS) and Santa Maria da Serra (SM), situated along the river Tietê in the State of São Paulo, Brazil. The villages lack basic public infrastructures and services, such as roads, public water supply, electricity and public health services. Multiple fecal samples were collected from 88 individuals in PS and from 38 individuals in SM, who were asymptomatic at the time of sampling and had no recent history of diarrheal disease. To gain insights into potential transmission routes, 49 dog fecal samples (38 from PS and 11 from SM) and 28 river water samples were also collected. All samples were tested by microscopy and PCR was used to genotype isolates of Giardia duodenalis, Blastocystis spp., Dientamoeba fragilis and Cryptosporidium spp. By molecular methods, the most common human parasite was Blastocystis spp. (prevalence, 45% in PS and 71% in SM), followed by D. fragilis (13.6% in PS, and 18.4% in SM) and G. duodenalis (18.2% in PS and 7.9% in SM); Cryptosporidium spp. were not detected. Further, G. duodenalis was found in 4 dogs (10.5%) in PS and 2 dogs (18.2%) in SM, whereas a single dog was found infected with Cryptosporidium canis. River water samples processed by filtration and immunomagnetic separation and examined by fluorescent microscopy, were negative for Cryptosporidium oocysts and Giardia cysts. Sequencing of the barcoding region of the small subunit ribosomal gene revealed large genetic variation among Blastocystis isolates, with subtypes (STs) that ...

Muitas espécies de protozoários podem causar gastroenterite aguda ou crônica em seres humanos e são altamente prevalentes nas populações residentes nos países em desenvolvimento, onde a transmissão é favorecida devido a condições precárias de higiene e escassa disponibilidade de água potável. No entanto, a infecção assintomática e o poliparasitismo também são comumente observados nessas populações. Neste trabalho, investigou-se a prevalência de protozoários intestinais em duas colônias de pescadores, Porto Said (PS) e Santa Maria da Serra (SM), situadas ao longo do rio Tietê, no Estado de São Paulo. As colônias não dispõem de serviços públicos básicos como: vias públicas, fornecimento de água e luz e saneamento básico. Todos os colonos (n = 88 em PS, e n = 38 em SM) coletaram três amostras de fezes, e todos eram assintomáticos no momento da coleta. Para obter informações sobre as possíveis vias de transmissão, amostras fecais de 49 cães (38 de PS e 11 de SM) e 28 amostras de água do rio foram coletadas (16 de PS e 12 de SM). As amostras fecais humanas e caninas foram analisadas por microscopia e PCR para detectar e caracterizar os protozoários Giardia duodenalis, Blastocystis spp., Dientamoeba fragilis e Cryptosporidium spp. Diante dos resultados obtidos, Blastocystis spp. foi o parasita mais prevalente nas amostras humanas (45,4% em PS e 71% em SM), seguido por D. fragilis (13,6% em PS e 18,4% em SM) e G. duodenalis (18,2% em PS e 7,9% em SM), já Cryptosporidium spp. não foi detectado na população humana. Além disso, G. duodenalis foi detectado em quatro cães (10,5%) em PS e dois cães (18,2%) em SM, enquanto que um único cão foi detectado com Cryptosporidium canis. Nas 28 amostras de água previamente processadas pelos métodos de filtração e separação imunomagnética e examinadas por microscopia de fluorescência, oocistos de Cryptosporidium e cistos de Giardia não foram...
Keywords: Agua - Amostragem; Protozoario; Medicina tropical; Reação em cadeia da polimerase; Protozoa